Metodologiczne problemy historii powojennego dokumentu filmowego w Polsce - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
The Methodological Problems of Studies on the History of Polish Postwar Documentary The author discusses the narratives and stereotypical (ideological) point of view as a matrix for constructing an overly simple image of the Polish documentary in the postwar period (1944–1955) as shadowed in the untruth of political discourse. In Marek Hendrykowski’s opinion this particular period in Polish documentary film was much more complicated and multi perspectived (in a “dialogical” sense) as a research object posing new questions and opening new perspectives for film historians.